GREEN WAKAF: STRATEGI PEMANFAATAN INSTRUMEN KEUANGAN ISLAM UNTUK KEBERLANJUTAN LINGKUNGAN - Fahmi Makraja; Rahayu Apridayanti; Ilham Akbar Shalahuddien; Raihan Putri; Mirza Al Fajri (EKOMBIS: JURNAL FAKULTAS EKONOMI, 2026)
Waqf is an Islamic financial instrument that has great potential to contribute to social and economic development. However, its utilization in the context of environmental sustainability, or what is known as Green Waqf, is still not optimal. This study aims to analyze strategies for utilizing the wakaf instrument to support environmental sustainability through Green Wakaf. The research method employed is a qualitative literature review, examining various concepts of wakaf, green finance, and their implementation in various countries. The results of the study indicate that there are several strategies that can be applied to optimize Green Wakaf. First, a funding strategy, which involves combining cash wakaf and productive wakaf to finance environmentally friendly projects such as renewable energy, waste management, and organic farming. Second, a partnership strategy, which involves collaborating between wakaf institutions, the government, the private sector, and civil society to increase the scale and impact of projects. Third, product innovation strategy, namely by developing new waqf models that are relevant to environmental issues, such as green stock waqf and green sukuk. The implementation of these strategies is expected to make Green Waqf an effective Islamic financial instrument to promote sustainable development. Thus, waqf not only plays a role in poverty alleviation, but also becomes a concrete solution in overcoming global environmental challenges.Keywords: Waqf, Islamic Finance, Green Waqf, Environmental Sustainability, Green Finance.